2008
DOI: 10.4103/0301-4738.39115
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve sheath decompression for visual loss in intracranial hypertension: Report from a tertiary care center in South India

Abstract: Aim:Severe visual loss is the only serious complication of intracranial hypertension secondary to idiopathic intracranial hypertension (IIH) and some cases of cerebral venous thrombosis (CVT). Optic nerve sheath decompression (ONSD) has been shown to improve or stabilize visual function in patients with IIH, while its role in CVT is yet to be established. We report our experience with optic nerve sheath decompression for visual loss in IIH and CVT.Materials and Methods:In this prospective noncomparative, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…We considered the number of eyes as the number of patients for calculation consistency. Nithyanandam et al 36 reported complications in terms of percentages, which we had to convert. In studies in which values of certain parameters were marginally available (eg, CSF pressure Ͼ40 cm of H 2 O in 73% of cases in the CSF diversion study by El-Saadany et al, 57 ), values were pre-sented as "NR" or not reported in On-line 3 and excluded from the mean CSF pressure.…”
Section: Limitationsmentioning
confidence: 99%
“…We considered the number of eyes as the number of patients for calculation consistency. Nithyanandam et al 36 reported complications in terms of percentages, which we had to convert. In studies in which values of certain parameters were marginally available (eg, CSF pressure Ͼ40 cm of H 2 O in 73% of cases in the CSF diversion study by El-Saadany et al, 57 ), values were pre-sented as "NR" or not reported in On-line 3 and excluded from the mean CSF pressure.…”
Section: Limitationsmentioning
confidence: 99%
“…20,22,52 Following ONSF, visual acuity stabilized or improved in 94% of eyes and deteriorated in 6% of eyes in 2 studies. 52,53 ONSF in the pediatric population improved visual acuity in two-thirds of patients, and vision worsened in 17% of patients. 54 Some groups propose the use of venous sinus stent placement to treat IIH on the basis of several imaging studies showing stenosis of the cerebral venous sinuses and the presumption that venous outflow obstruction constitutes the underlying etiology of most cases of IIH.…”
mentioning
confidence: 99%
“…3 However, there is a considerable rate of reoperation, 10%-32%, due to failure of the initial procedure and progression of the disease. 3,6 Orbital cellulitis has also been reported. 5 However, most of the complications are trivial and not visually significant.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The procedure carries the risk of certain complications, which may be up to 45%. 6 Unfortunately, the procedure may result in permanent and severe loss of vision in less than 2% of cases. The most commonly reported complications include diplopia due to manipulation of extraocular muscles during the procedure, mainly the medial rectus, atonic pupil, and anisocoria that are believed to be due to interruption of the blood supply to the ciliary ganglion.…”
Section: Discussionmentioning
confidence: 99%